PENINGKATAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN PENDEKATAN PEMBELAJARAN AKTIF MENGGUNAKAN STRATEGI TUTOR SEBAYA - Halima Ina Ose; St. Muthmainnah Yusuf; Nia Kurniaty Rukman (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
This research is intended to find out how much student’s achievements are by applying peer tutoring strategies in mathematics in class VIIG MTs N Kota Kupang City. The study used was a qualitative study with the learning strategy applied was a Peer Tutoring Strategy. The research subjects were Grade VIIG students of MTs N Kota Kupang City in the 2019/2020 academic year totaling 31 students the observed and measured variable in the student’s mathematics learning achievement. The results of the study explained that increasing student mathematics leraning achievement in the learning process that is with peer tutoring strategies learning with peer tutors is learning done with student peers.